PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP TURNOVER INTENTION PEGAWAI PADA PUSKESMAS MANGGENG ACEH BARAT DAYA - Muhammad Luthfi; Husnaina Mailisa Safitri; Zikrilah (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
This study aims to determine the effect of workload and work stress on employee turnover intention at Puskesmas Manggeng Southwest Aceh. The method used is the causality method which aims to explain the effect of the independent variable on the dependent variable. Determination of the sample of this study using saturated sample technique. The sample used in this study were 72 employees at the Puskesmas Manggeng Southwest Aceh and were willing to be respondents. The analysis method applied is multiple linear regression analysis. The results showed that workload partially had a positive and significant effect on employee turnover intention at Puskesmas Manggeng Southwest Aceh. Work Stress partially has a positive and significant effect on employee turnover intention at Puskesmas Manggeng Southwest Aceh. Workload and work stress simultaneously have a positive and significant effect on employee turnover intention at the Puskesmas Manggeng Southwest Aceh. Increased turnover intention is determined by workload and work stress. The more the workload felt by employees decreases and the lower the level of work stress experienced by employees, the greater the opportunity for the Puskesmas Manggeng Southwest Aceh in reducing employee turnover intention Keywords : Workload, Job Stress, Turnover Intention